2017
DOI: 10.1108/jfmm-11-2016-0101
|View full text |Cite
|
Sign up to set email alerts
|

Media and sustainable apparel buying intention

Abstract: Purpose Using the theory of planned behavior, the purpose of this paper is to examine the relationships between different types of media and the intention to buy sustainable apparel and test whether attitudes, social norms, and self-efficacy beliefs may explain these relationships. Design/methodology/approach A cross-sectional survey study was conducted among 681 young adults (18-26 years old). Findings Exposure to social media content of sustainable organizations, eco-activists, and sustainable apparel br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 52 publications
3
67
0
1
Order By: Relevance
“…The study's finding that emotion of guilt affects avoiding purchasing high-priced luxury clothing products; is similar to the research results showing that quilt affects hedonistic consumption (Okada, 2005;Chun et al, 2007) and avoiding high-priced purchasing products (Nowlis & Simonson, 1996). This result is consistent with research results showing that consumers can prefer low-priced products (De Lenne & Vandenbosch, 2017) to reduce guilt. This result is similar to Ki et al's (2017) research results showing that the guilt emotion decreases the repeat purchasing behaviour of the consumer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The study's finding that emotion of guilt affects avoiding purchasing high-priced luxury clothing products; is similar to the research results showing that quilt affects hedonistic consumption (Okada, 2005;Chun et al, 2007) and avoiding high-priced purchasing products (Nowlis & Simonson, 1996). This result is consistent with research results showing that consumers can prefer low-priced products (De Lenne & Vandenbosch, 2017) to reduce guilt. This result is similar to Ki et al's (2017) research results showing that the guilt emotion decreases the repeat purchasing behaviour of the consumer.…”
Section: Discussionsupporting
confidence: 88%
“…At this point, hedonistic goods and services (Okada, 2005;Chun et al, 2007) and because of the features perceived as unnecessary, consumers can avoid buying high-priced products (Nowlis & Simonson, 1996). Although consumers get from luxury consumption some pleasure, they can reduce their fancy or luxury consumption to balance their guilt and prefer more sustainable and low-priced products (De Lenne & Vandenbosch, 2017). Ki et al's (2017) research-based on "balance theory", which is claimed that human happiness is affected by negative emotions as well as positive emotions; demonstrated that guilt as a negative emotion affects the consumer's repeat purchasing behaviour of luxury products (Ki et al, 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Hızlı modanın olumsuz etkilerinin hem üretici hem tüketici tarafından görülmesiyle, sürdürülebilir moda kavramı ön plana çıkmıştır. Sürdürülebilir moda perakendeciliği literatürü yoğun olarak tüketicilerin sürdürülebilir moda ürünleri satın alma niyeti ile ilişkili faktörleri nicel yöntemle incelemiştir (Kim & Jin, 2019;de Lenne & Vandenbosch, 2017;Wei, & Jung, 2017;Min Kong, & Ko, 2017;Han, & Stoel, 2016;Cho, Gupta, & Kim, 2015;Chan, & Wong, 2012;Manchiraju vd., 2012;Hustvedt & Dickson, 2009). Günümüzde her alanda olduğu gibi, moda sektöründe de sürdürülebilirliğe ilginin artmasına, hem tüketicilerin, hem de perakendecilerin bu konuyla ilgili farkındalığının oluşmasına rağmen, tüketicilerin sürdürülebilir moda perakendeciliğine yönelik algılarının nasıl şekillendiği henüz netleşmemiştir.…”
Section: Sürdürülebilir Moda Perakendeciliği: Tüketici Algıları üZerine Bir Araştırmaunclassified
“…Recent empirical studies of social media in the fashion context focus on employing primary data to identify trends and examination of consumer interaction using traditional methods such as surveys and interviews (e.g. Kang and Kim, 2017;De Lenne and Vandenbosch, 2017;Nash, 2019). However, complex, user-generated social media data, which are valuable for problem solving in fashion contexts, presents challenges for research designs that rely on conventional methods (Tsou, 2015).…”
Section: Introductionmentioning
confidence: 99%